2020
DOI: 10.3390/nu12103122
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Activation and Antioxidative Defense Are Interrelated and Moderately Modified by n-3 Polyunsaturated Fatty Acid-Enriched Eggs Consumption—Double-Blind Controlled Randomized Clinical Study

Abstract: This placebo-controlled, double-blind, randomized, interventional study investigated the effects of low/intermediate doses of n-3 polyunsaturated fatty acids (PUFAs) on the endothelial function, markers of leukocyte activation, and oxidative status following dietary intake of n-3 PUFA-enriched hen eggs in young healthy individuals. Twenty young healthy adults of both sexes who consumed n-3 PUFA-enriched hen eggs (two eggs per day, for three weeks, total of approximately 407 mg/day n-3 PUFAs) or regular eggs (t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 68 publications
1
10
0
Order By: Relevance
“…In addition, a Mediterranean type of diet that is rich in n-3 PUFAs is associated with lower levels of oxidative stress biomarkers and is widely recommended not only to cardiovascular patients but to the general population as well [ 42 ]. Interestingly, low or medium doses of n-3 PUFA intake in the form of enriched hen eggs increase superoxide dismutase (SOD) levels in young and healthy individuals, indicating that n-3 PUFAs could be involved in the physiological processes associated with oxidative balance in healthy individuals [ 22 ]. The present results demonstrated that intake of n-3 PUFA-enriched hen eggs significantly decreased GPx activity but did not affect TBARS (a measure of oxidative stress) and FRAP (a measure of antioxidant capacity) levels in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, a Mediterranean type of diet that is rich in n-3 PUFAs is associated with lower levels of oxidative stress biomarkers and is widely recommended not only to cardiovascular patients but to the general population as well [ 42 ]. Interestingly, low or medium doses of n-3 PUFA intake in the form of enriched hen eggs increase superoxide dismutase (SOD) levels in young and healthy individuals, indicating that n-3 PUFAs could be involved in the physiological processes associated with oxidative balance in healthy individuals [ 22 ]. The present results demonstrated that intake of n-3 PUFA-enriched hen eggs significantly decreased GPx activity but did not affect TBARS (a measure of oxidative stress) and FRAP (a measure of antioxidant capacity) levels in patients with CAD.…”
Section: Discussionmentioning
confidence: 99%
“…Our recently published work showed that consumption of two n-3 PUFA-enriched hen eggs per day for three weeks (~410 mg of n-3 PUFAs per day) had immunomodulatory effects, without affecting the reactivity of peripheral microcirculation in healthy young subjects [ 22 ]. However, an increased amount of n-3 PUFAs in the daily diet to 1053 g of n-3 PUFAs/day for 3 weeks increased serum free n-3 PUFA concentration and enhanced skin microvascular reactivity while reducing proinflammatory and increasing anti-inflammatory cytokine serum concentration in healthy young subjects [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…n-3 PUFA-enriched hen eggs were produced according to the protocol of research group from Faculty of Agrobiotechnical Sciences, University of Osijek ( Stupin et al, 2018a ; Stupin et al, 2020 ; Mihalj et al, 2020 ). In brief, soybean oil (5%) fed to laying hens in feed was replaced with a mixture of fish (1.5%) and linseed (3.5%) oil.…”
Section: Methodsmentioning
confidence: 99%
“…In brief, soybean oil (5%) fed to laying hens in feed was replaced with a mixture of fish (1.5%) and linseed (3.5%) oil. Preparation and analysis of samples (feeding mixtures for laying hens and edible parts of eggs) to determine fatty acid content was performed in accordance with our well-established protocols, which are described in detail in previous publications ( Stupin et al, 2018a ; Stupin et al, 2020 ; Mihalj et al, 2020 ). Portions of saturated fatty acid, monounsaturated fatty acid, n-6 PUFAs, and n-3 PUFAs were determined in g/100 g of total fatty acids in feed, and in mg/100 g in eggs (edible part), as previously described ( Stupin et al, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…N-3 PUFAs did not improve plaque burden, morphologic vessel characteristics or lipid burden. A human controlled-randomized clinical trial in young, healthy individuals revealed markers of leukocyte activation (such as CD11a/LFA-1) and antioxidative defense to be related to an increased intake of n-3 PUFAs [45]. Furthermore, n-3 PUFA consumption induced a significant shift towards antiinflammatory prostanoids and increased levels of pro-resolving oxylipins and increased TGFβ-1 and reduced interleukin 6 secretions by peripheral Th17 cells.…”
Section: The Effect Of N-3 Pufas On Inflammatory and Prothrombogenic ...mentioning
confidence: 99%